'They are treating us with contempt': The complexities of opposition in an English village. (May 2019) - Harrison, Elizabeth
Abstract: This article is an ethnographic examination of the response to proposed housing development in an English village which provides broader insights into the nature of democratic and decision-making processes around local development projects. Dissecting the complexities of class, age and length of residence, it argues that attributions of either 'NIMBYism' or 'community cohesion' simplify how and why people come together. Charges of NIMBYism in popular representation seek to exploit difference through certain well-established tropes. These often distinguish between the interests of poorer and longer-established residents with livelihoods rooted in rural areas, and those of wealthier people with urban-based livelihoods for whom rural housing is a lifestyle choice. Academic discussions of NIMBYism have sought to unpack the complexity of opposition, identifying problems in the uncritical use of the term. In contributing to this literature, I argue that it is important to consider how responses are shaped by both a combination of individual interest and sense of investment in place. I suggest that 'community' is an effective organising device for protesters that can obscure numerous differences and that the nature of political process and consultation also are crucial factors in shaping opposition. Concerns with the nature of nominally democratic processes and the role of outsider imposition are especially significant here. Highlights: The article is an ethnographic examination of opposition to a housing development in an English village. Ideas of both 'NIMBYism' and 'community cohesion' simplify why people come together in response to development plans of external origin. The intersection of individual interests with the nature of consultation plays an important role in responses to development planning. Narratives of community are used strategically to galvanise opposition in ways that obscure difference.